A cultura como mediadora do desenvolvimento das funções psíquicas superiores na criança: a atividade docente de musicalização na Educação Infantil - Souza, Carlos Eduardo de (Universidade Federal de São Carlos, 2012)
The present work discusses culture as promoting the development of humanity in humans. The concept of culture working is based on the marxist concept that comprises with culture all production developed by humankind throughout its history. The Historic-Cultural Perspective developed by Vigotsky, based on the theoretical assumptions of dialectical and historical materialism of Marx, was used as a theoretical framework for understanding how culture transforms the humans, modifying its natural functions in higher mental functions. In the methodology we seek to draw a relationship between the historical-cultural theory and its grounding marxist, demonstrating how Vigotsky use of dialectical materialist method in carrying out his studies on the human psyche. In the methodological procedures is presented the form of data collection, which characterizes this research of bibliographic nature, showing what were the criteria for selection of theses and dissertation that were analyzed. In data analysis we seek to demonstrate through the performance of the teacher in the process of teaching music, as he in his mediating activity can promote the chidren s access the culture and, how he, making his practice in the zone of proximal development can enhance the development in of higher mental functions. We discussed how the child in their activity mediated by intencional social relations (in this case, the musicalization at school) and access to culture, develops higher mental functions, unique to humans. Keywords:
Keywords: Educação; Teoria histórico-cultural; Cultura; Funções psíquicas superiores; Atividades de musicalização; Educação infantil; Historical-cultural theory; Culture; Higher psychical functions; Musicalization; Early Childhood Education; CIENCIAS HUMANAS::EDUCACAO